Rektor C.J.L. Almqvist och personlighetsprincipen - Ullman, Annika (Nordic Journal of Educational History, 2014)
Principal C.J.L. Almqvist and the principle of personality The Swedish author and visionary Carl Jonas Love Almqvist (1793–1866) was the principal for twelve years (1829–1841) of the government-initiated pilot school ”Nya Elementarskolan” (New Elementary School) in Stockholm. In this position, he argued that both the school and the state should be built on the same basic idea: the right of individual freedom. This argument is often referred to as ”personlighetsprincipen” (the principle of personality), a concept launched by another prominent figure of the liberal culture of the time, Erik Gustaf Geijer (1783–1847). This article explores how the principle of personality is expressed in the texts of Almqvist and is mainly built upon the concept’s allegorical resources. It examines the thesis that Almqvist’s use of the term is best understood if one distinguishes between the political, pedagogical, and existential dimension of the concept. The article ends with some thoughts about the context of the concept and a discussion on whether Almqvist had a greater interest in personalities than in principles.